CEO archetype identity drives organization culture - Prince, Melvin; Forr, James; Wardlaw, Jim; Plummer, Joseph (Journal of Leadership Studies, 2019)
In the current study the relationships between CEO archetypes and organizational climate were examined. Archetypes are historical, mythical, and cultural representations that are shared in our collective unconscious. Data were collected from a CEO and his employees, using a mixed methods research approach which involved the Zaltman Metaphorical Elicitation Technique (ZMET), as well as personality measures and quantitative assessments of organizational climate. The CEO archetype as perceived by employees is that of a benevolent patriarch which mirrors the CEO's self-concept as caring for the well-being of employees. Employees ascribed the stress-free and nurturing organizational climate to the CEO's archetypical leadership style. However, their organizational climate, in principle, leads to excessive employee familistic dependence on the CEO for making important organizational decisions and supplying creative ideation. The present study of a CEO archetype and its bearing on organizational climate is unique, filling an important gap in management knowledge. Implications of the study involve the channeling of its insights about the archetype-embedded organizational climate, so as to better select administrative managers, improve organizational communication trust and openness, stimulate creative innovation, handle organizational crises, and generally promote employee well-being. © 2019 University of Phoenix
Keywords: dept.mkt; peer-reviewed

The moral bases of consumer ethnocentrism and consumer cosmopolitanism as purchase dispositions - Prince, Melvin; Yaprak, Attila N.; Palihawadana, Dayananda (Journal of Consumer Marketing, 2019)
Purpose: This paper aims to develop a model that explains the moral bases of consumer ethnocentrism and consumer cosmopolitanism as purchase dispositions. The authors build their work on moral foundations theory and the social theories of Emile Durkheim. Design/methodology/approach: Theory-building from general theories of motivation is grounded in cultural norms, and empirical research is conducted to test theoretical propositions. Findings: The focus is on the theoretical implications of binding or individualism morals of consumers within social groups. Consequently, variables in the model relate to ethical themes of community, autonomy and divinity. This theory posits that, for a variety of considerations, loyalty has a direct and positive effect on consumer ethnocentrism and on consumer cosmopolitanism. Serendipitously, other moral foundations have negative effects. The authors theorize that negative relationships exist between authority and consumer cosmopolitanism, and between sanctity and consumer ethnocentrism. This model also illustrates that consumer ethnocentrism positively predisposes favorable domestic product judgments. Research limitations/implications: New ethical factors in consumer dispositions affecting product purchase decisions are explored. Hypotheses can be empirically replicated and moderated in future research. Practical implications: Marketers can use the variables of personal values, moral foundations and gender role identity to fashion marketing communications and to target selective consumer segments. Social implications: The persuasion process of social marketing will be enhanced by understanding relevant motives. Originality/value: The use of the fine-grained moral foundation antecedents to predict consumer predispositions of ethnocentrism and cosmopolitanism is without precedent. © 2019, Emerald Publishing Limited.
Keywords: Consumer ethics; Consumer ethnocentrism; Consumer psychology; dept.mkt; peer-reviewed

Consumer morality and moral consumption behavior: literature domains, current contributions, and future research questions - Yaprak, Attila; Prince, Melvin (Journal of Consumer Marketing, 2019)
Purpose: The literature on consumer morality and consumption is spread widely across many research streams and would benefit from grouping under selected themes so that scholars’ work can be guided by the compass of these themes. It is also important to add studies to each of these themes to serve as gateways that will guide new research. The aim of this special issue of the Journal of Consumer Marketing was to achieve precisely this purpose. The purpose of this paper is to open the gate to the exploration of the themes that today describe this landscape. Design/methodology/approach: The paper assesses the contributions made in each of several domains to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. There are at least four domains of morality and moral consumption studies as follows: the formation of the moral self and moral identity; moral identity and ethical consumption; moral reasoning (cognitive processes) and moral choice; and the moral self and marketing. Each of these domains of work provides insight into the moral consumption phenomenon. Findings: The authors highlight the development of the moral self and underscore the significance of the relationship between identity development and the individual’s moral actions and by extension the significance of that relationship in moral consumption. Also, the paper adds to the current discussion on morality and ethical consumption by underscoring their interlinked nature and how that linkage can drive consumption behavior, highlight the cognitive processes involved in moral choices and how consumers reason to arrive at those choices. Finally, the authors provide examples of the workings of moral identity and reasoning in consumption contexts more directly. Originality/value: Each of these morality and moral consumption domains of work provides unique insights into the moral consumption phenomenon; thus, it is important to disseminate the contributions made in each domain to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. In this paper, the authors offer contemporary original samples of key contributions to each of these domains. © 2019, Emerald Publishing Limited.
Keywords: Consumer morality; Ethical consumption; Moral choice; Moral consumption; Moral identity; Moral reasoning; dept.mkt; peer-reviewed

Political economy of farm loan waivers in India - Jha, Srirang; Mohapatra, Amiya Kumar; Lodha, Shyam S. (FIIB Business Review, 2019)
Political leadership of various states in India is under tremendous pressure to provide instant relief to the farmers reeling under debt trap, resulting in suicides in several cases. Often, suicides by peasants are widely covered in the media which in turn sway the people’s perception about apparent indifference of the government towards the farming communities of the country. This certainly brings in concerns related to political economy revolving around judicious distribution of wealth and national income of the country. State governments of India are generally reluctant to waive off the farm loans as a matter of routine due to concomitant burden on exchequer that might adversely affect their fiscal balances. However, political parties tend to use farm loan waiver as tactics to come to power in spite of the fact that such populist measures are not good for the economy, nor do they offer a long-term solution to the age-old problem of higher degree of incidence of indebtedness among the farming communities. This article explores the antecedents and consequences of farm loan waivers and the way forward. Besides, it also reconnoitres whether the state takes such decisions as farm loan waiver purely on the basis of economics or any hidden political agenda.
Keywords: dept.mkt; peer-reviewed

The Diogenes Effect in retail buyer information processing - Prince, Melvin; Kwak, Lynn; Priporas, Constantinos Vasilios (Journal of Retailing and Consumer Services, 2019)
The search for an ethical vendor who is honest and trustworthy in the exchange process is conceptualized as the Diogenes Effect, an innovative concept. In the light of this effect, the theoretical framework of the current study's model involved retail buyer responses to vendor persuasive communications. The model was tested by having a sample of retailer buyers complete a survey of information processing in the search for a product and vendor. This study innovatively links vendor communication effects to retailer buyer decision-making and evaluations by incorporating and integrating elements of Elaboration Likelihood Theory. Contributing to theory-building, it was found that when retailer buyers searched for a vendor with an ethical orientation, the result was intensified central processing of information and decreased peripheral information processing. This was especially salient when retailer buyers had greater longevity of professional experience. The next stage, information processing, led to feedback that enabled assessment of vendor trustworthiness. Finally, the research measured the level of fulfillment in the post-purchase phase. In the end, typical outcomes included the generation of favorable expectations of vendor performance, as well as the positive impact of those heightened favorable expectations on greater satisfaction with the value ultimately received from the vendor.
Keywords: Diogenes; Diogenes effect; Elaboration likelihood model; Expectations; Information processing; Retailer buying decision; Satisfaction; decision making; dept.mkt; information processing; modeling; peer-reviewed; retailing